Defining health and disease: Self-knowledge as a standard of health - Αθανασιάδης (Grigoris Athanasiadis), Γρηγόρης (Bioethica, 2015)
A central issue in the philosophy of medicine is to solve the problem of determining the nature of the concepts of health and disease. Some theorists claim that health and disease are purely value-free and descriptive concepts that are discoverable and grounded in the biological and medical sciences. Others claim that health and disease are essentially value-laden concepts, i.e. healthy states are those states we (individuals, groups, societies) desire or value and diseased states are those we want to avoid or disvalue. Considering the longtime disagreement among physicians, theorists of health and philosophers about the essential characteristics of health and disease, the aim in the first part of this paper is to briefly present four different philosophical approaches of health and disease in an attempt to introduce the readers to the debate. This article begins with the Biostatistical theory of Christopher Boorse. It turns to the Malady theory of Danner Clouser, Charles Culver and Bernard Gert, the holistic theory of Lennart Nordenfelt and finally the adaptation theory of József Kovács. In the second part of the paper, some objections will be stated to each theory. In the third and last part, a completely different account of health will be given, which holds that self-knowledge is a criterion of human health. Health, unlike disease, is not a state or a condition of the organism but an endless process. Its essence can be better captured in philosophical rather than medical terms and it should be applied only to human beings.